Multicultural Perspectives in Music Education - Anderson, William M.; Campbell, Patricia Shehan (R&L Education, 2011)
With Multicultural Perspectives in Music Education, you can explore musics from around the world with your students in a meaningful way. Broadly based and practically oriented, the book will help you develop curriculum for an increasingly multicultural society. Ready-to-use lesson plans make it easy to bring many different but equally logical musical systems into your classroom. The authors-a variety of music educators and ethnomusicologists-provide plans and resources to broaden your students' perspectives on music as an important aspect of culture both within the United States and globally.
Keywords: Multicultural education; Music -- Instruction and study; World music -- Instruction and study; Music; Music, Dance, Drama & Film; Music Instruction & Study